Non-implant associated primary breast anaplastic large cell lymphoma in a postpartum female - Banka, Sweta; Dhakate, Nishad; Rajput, Manjit (Indian Journal of Case Reports, 2025)
Anaplastic large cell lymphoma (ALCL) is an aggressive peripheral T-cell non-Hodgkin lymphoma. Breast implant-associated ALCL is a rare subtype of ALCL, now designated as a separate entity under the latest 5th edition of the World Health Organization classification of hematolymphoid tumors. ALCL of the breast in a patient without a breast implant is an even rarer subtype. We here report a case of pathologically proven primary ALCL of the breast diagnosed during the postpartum period. The patient achieved a complete metabolic response after six cycles of rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone. It is essential to recognize this entity because the management is completely different from the more common adenocarcinoma, which is treated with surgery and radiation, unlike lymphoma, which is treated with chemotherapy alone. We reviewed the literature and identified 30 cases of non-implant-associated Primary Breast ALCL. Our case was unique in being postpartum in presentation and involving bilateral breasts.